Использование дентального операционного микроскопа и модифицированного никель-титанового зонда в зубосохраняющем эндодонтическом лечении зуба, ранее восстановленного с помощью анкерного штифта (Эндодонтия Today)
This paper presents a complex clinical case of repeated endodontic treatment of tooth 1.1, previously irrationally restored with brass post and defective sealing of the root canal. Treatment became possible through the use of an operating microscope in dental clinic, which allows to specify the anatomical structure of root canal in conditions of magnification and adequate illumination what facilitates the execution of all basic stages of preparation, including cleaning the root canal from the brass pin and a gutta-percha fragmented components. Before sealing the canal was additionally processed with ozone.